Percutaneous coronary intervention patients' and cardiologists' experiences of the informed consent process in Northern England: a qualitative study. Issue 6 (24th June 2017) - Probyn, Joy; Greenhalgh, Joanne; Holt, Janet; Conway, Dwayne; Astin, Felicity
Abstract : Objective: Informed consent is central to ethical medical practice, but little is known about how the process takes place in clinical practice. Percutaneous coronary intervention (PCI) is a common revascularisation procedure. Studies report that patients overestimate benefits, forget the risks and are unaware of alternative treatments. The aim of this study was to describe PCI patients' and cardiologists' experiences of the informed consent process in acute care settings. Design/setting/participants: A qualitative study with a maximum variation sample of elective and acute PCI patients and cardiologists taking their consent, recruited from a district general hospital and tertiary centre. In-depth interviews were conducted, and consent discussions were audio recorded. Data collection, coding and theorising occurred simultaneously. Findings: Forty-one (26 male) patients scheduled for elective (20) or urgent (21) PCI and 19 cardiologists (5 female) participated. Despite diversity in patients' experiences of informed consent, elective and acute patients experienced a common four-stage process of consent. Most patients made the decision to have treatment at PCI referral and took a passive role in the discussions we recorded. They recognised cardiologists as experts, trusted the medical system to 'fix' their health problem and were unaware of their role in the informed consent process. Informed consent discussions functioned as a formal 'event', enabling cardiologists to check patients' understanding and enabling patients to access treatment. Conclusions: The configuration of services and patients' perceptions of their role in informed consent underpin a mismatch between legal and ethical principles of informed consent and current practice. The variation in patients' experiences of the current place of informed consent in service delivery represents a missed opportunity for cardiologists to work in decision-making partnerships with patients. In light of recent changes in the law, a new approach to informed consent is required.